Evaluasi Penerapan Good Corporate Governance (GCG) untuk Mewujudkan Pekerjaan Layak di PT Indo Gunta dalam Mendukung SDGs 8 - Ayu Noviana, Franciska Diah; Dwiki Akbar, Muhammad (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to evaluate the implementation of Good Corporate Governance (GCG) at PT Indo Gunta to support the achievement of Sustainable Development Goals (SDGs) 8, which focuses on creating decent work and sustainable economic growth. Quantitative methods were applied to collect data through valid and reliable questionnaires. Then, the data was analyzed using simple linear regression. With a regression coefficient of 0.345 and a significance p-value of 0.05, the research findings show that the implementation of GCG principles such as transparency, accountability, and fairness has a significant positive impact on the quality of decent work. This result shows that GCG is not only a tool to comply with regulations, but also an important method to create a more inclusive, healthy, and equitable work environment. This research provides benefits for companies to improve aspects of employee training and access to information to support social and economic sustainability.